The Brachyura described by John Robert Kinahan, and a discussion on Kinahan’s overlooked authorship of the family-group name Litocheiridae (Crustacea: Decapoda) - Low, Martyn E. Y.; Monaghan, Nigel T.; Holmes, J. M. C. (Zootaxa, 2012)
John Robert Kinahan (b. 1828, d. 1863) published new names for Brachyura collected from Australia, Ireland and Peru inthree publications. The dates of publication of these papers have not been previously determined accurately and some wereissued as separates and/or issued in multiple journals. The dates of these publications are determined, and a list of allknown new names proposed by Kinahan for the Brachyura (and their current identities) is provided. Kinahan is also de-termined to be the author of the family-group name Litocheiridae by an overlooked set of criteria making the name available in 1856.